Psychological Analysis of Georgia Cotton in Ticket to Paradise Movie - Wicahyani, Kadek Fania Natasya; Agung, I Gusti Ayu Mahatma; Daeli, Ritueli (Jurnal Lingua Idea, 2023)
A movie is a medium to convey a story that is packed in the form of moving pictures. Conflicts that appear in a movie can influence the psychological aspect of the character, especially the motivation of each character to do something after facing a conflict or having a problem. This study was conducted to analyze how psychological aspects affect the character’s feelings and behavior in a movie entitled “Ticket to Paradise”. This study applied a qualitative method. The data were collected by note-taking the scene in the movie that contained psychological aspects of Georgia Cotton. The study focused on the data that showed action triggered by psychological aspects. The data were categorized and analyzed using Bernhardt's theory of the psychological aspect of human motivation (1945). The findings were presented in a table and explained descriptively. This study identified that the aspect of organic needs or appetites should be fulfilled to reach Georgia’s satisfaction, the aspect of wants could influence Georgia to solve a problem, Georgia’s behavior was affected by the aspect of emotion, the aspect of feeling and experience influenced Georgia in making a decision, and social motives shown by Georgia as a social creature in a society.